Impact Of Cross-Linking Polymer To Bridge The Porous Membrane And Selective Layer In Membrane Absorption - Adnan, Nur Sajha (Universiti Sains Malaysia, 2022)
The membrane gas absorption (MGA) technology has been an attractive alternative discovered by the researchers to remove the carbon dioxide (CO2) gas from releasing into the atmosphere. Various modifications of the membranes used as the contactor in this technology has become the focus of the researchers to improve the MGA performance. In this thesis, polyvinylidene fluoride (PVDF) was used as the support membrane to study the effect of cross-linking the membrane and the polymers in MGA. A porous PVDF membrane was fabricated through the non-solvent induced phase separation (NIPS) or commonly known as the immersion precipitation method. The modification of this PVDF membrane was done by dip-coating the membranes into chitosan, nylon, dopamine and ethylenediamine (EDA) polymers. The modified membranes were studied to determine the feasibility of the modified membranes in MGA. FTIR, porosity and pore size distribution were used to characterize the fabricated unmodified and modified PVDF membranes. The SEM images of the modified PVDF membranes with different polymers shown similar porous structures to the unmodified PVDF membrane. The porosity of the unmodified PVDF membrane obtained was 78.02%. Meanwhile, the porosity of PVDF/Chitosan, PVDF/Nylon, PVDF/Dopamine and PVDF/EDA membranes obtained were 81.28 %, 76.91 %, 81.75 % and 80.52 %, respectively. The pore size distribution of the modified membranes shown significant difference from the unmodified membrane. The MGA performances of the modified membranes were lower than the unmodified PVDF membrane. xiv PVDF/EDA membrane seemed to has the better MGA performance among the modified PVDF membranes and was used to study on the effect of various parameters of the EDA coating solution to the MGA performance. The PVDF membranes were coated with EDA polymer at various coating temperatures, times and concentrations. The PVDF membranes were coated with EDA polymer at coating temperature of 50˚C and 80˚C. The MGA performance of PVDF/EDA membrane coated at temperature of 80˚C was higher than the MGA performance of PVDF/EDA membrane coated at lower temperature. The coating time of EDA polymer were varied to 30 mins, 60 mins and 120 mins and the PVDF/EDA membrane with coating time of 120 mins had the better MGA performance. Meanwhile, the coating concentration of EDA polymer were varied to 0.5 M, 1.7 M and 3.0 M and similarly, the PVDF/EDA membrane at higher EDA concentration had the better MGA performance. This study showed that the cross-linking of the EDA polymer on the porous PVDF membrane impacted the MGA performance. Thus, it is an attractive potential to be employed in the MGA technology to reduce the emission of the CO2 gas into the atmosphere. Thus, this work can be developed further to enhance the MGA technology in reducing the emission of the CO2 gas into the atmosphere and promote the aim of sustainable development goal 13 towards coping with the climate change by urgent action in decreasing the emission of the CO2 gas.